2013
DOI: 10.1080/01919512.2012.758022
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Generation from Argon-Oxygen Mixtures in Presence of Different Packing Materials within Dielectric Barrier Discharge Gap

Abstract: Assessments of ozone yield and concentration in DielectricBarrier Discharge of argon-oxygen mixtures in presence of various packing materials are discussed. These include zeolite molecular sieve 13X pellets, Pyrex beads, Pyrex wool, and porous TiO 2 -beads, which presented differential reactive surfaces, nano cavities, photo-catalysis, and dissimilar ionic environments. Their utility was evaluated in conjunction with varied gas composition, flow rate, and electrical inputs. In a mixture of 3-21% O 2 in argon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Relative to that in the empty-bed reactor, the 'average width' of the discharge gap in the DBD reactor was reduced by packing particles; that is, the packing particles occupied part of the discharge gap volume, increasing the surface area of the medium and the pore structure complex; moreover, the formation of more micro-discharges contributed to the efficiency of ozone synthesis [22,29]. The O 3 concentration also increased, consistent with the results reported in the literature [30,31]. When particles were added into the DBD gap, the electric field intensity of the discharge area was altered, enhancing the discharge effect; meanwhile, the original discharge electric field was distorted [32].…”
Section: Experimental Setup and Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Relative to that in the empty-bed reactor, the 'average width' of the discharge gap in the DBD reactor was reduced by packing particles; that is, the packing particles occupied part of the discharge gap volume, increasing the surface area of the medium and the pore structure complex; moreover, the formation of more micro-discharges contributed to the efficiency of ozone synthesis [22,29]. The O 3 concentration also increased, consistent with the results reported in the literature [30,31]. When particles were added into the DBD gap, the electric field intensity of the discharge area was altered, enhancing the discharge effect; meanwhile, the original discharge electric field was distorted [32].…”
Section: Experimental Setup and Methodssupporting
confidence: 86%
“…When particles were added into the DBD gap, the electric field intensity of the discharge area was altered, enhancing the discharge effect; meanwhile, the original discharge electric field was distorted [32]. The difference in the degree of distortion was attributable to the difference in packing materials [31,33]. The relative dielectric constant of ZrO 2 is 27, and that of Al 2 O 3 is 9.2.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…Solid Materials Intended to Be Used as the Bed in a DBD Reactor DBD reactors and the application of non-thermal plasma are normally used for ozone generation, material treatment, particle reduction from exhaust, removal of NO X , CO X , particulate matter, pollutants, etc. [19][20][21][22][23][24][25]. Naturally, the selection of bed materials varies as per their respective application.…”
Section: Present Literaturementioning
confidence: 99%
“…Of the various DBD reactors, packed-bed reactors (PBRs) have flexible options for packing materials to remove pollutants (e.g. NO X , CO 2 , PM) or improve ozone synthesis [4][5][6][7][8]. Ray et al tested the conversion of CO 2 into CO by packing (glass beads, Al 2 O 3 , TiO 2 , CeO 2 ), and CeO 2 was found to result in the best conversion efficiency [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that PBRs can improve energy efficiency, yet their behavior is poorly understood. The material properties, including the capacitance, dielectric constant, and shape factor, can affect the discharge phenomena within the packed bed [4][5][6][7][8][9][10][11][12]. As PBRs are highly complex systems with many parameters, the optical techniques that are commonly used in other DBD systems are difficult to diagnose PBRs.…”
Section: Introductionmentioning
confidence: 99%